(untitled) (Philological Studies, 2019)
In this paper we will focus on the question what is the language? Linkage language with people who speak it, leads language and the study of language on genetics. We will consider synchrony and diachrony in researches in linguistics. Synchrony and diachrony in the context of the science of living beings. We will turn our attention to the diachrony in synchrony. We will ask the question what the language reveals to us? How to read the language? These questions leads us to the metaphorical notion of linguistic archeology.